First-time gardener : how to plan, plant & enjoy your garden - Tophill, Frances; Winfield, Clare (London : Kyle Books, 2022)
"Although excited by the prospect of moving into their own home for the first time, many people are mystified by the prospect of what to do with their outdoor space. Frances Tophill's fuss-free, practical guide shows you how to create a space outside your own back door that's designed by you, built by you and enjoyed by you."--
You & your garden -- Designing your garden -- Hard landscaping -- Planning beds & borders -- Choosing plants -- Fruit, vegetables & herbs -- Planting & maintenance.
Includes index.
Keywords: Gardening; Jardinage; gardening; Gardening